PHBV/bioglass composite scaffolds with co-cultures of endothelial cells and bone marrow stromal cells improve vascularization and osteogenesis for bone tissue engineering. Issue 36 (21st April 2017) - Wu, Jun; Wu, Zhi; Xue, Zhenqiang; Li, Haiyan; Liu, Jinbo
Abstract : PHBV + 10% BG composite scaffolds stimulated osteogenic differentiation and angiogenic differentiation of co-cultures of HBMSCs and HUVECs by enhancing paracrine effects between the two types of cells. Abstract : Polyhydroxybutyrate–polyhydroxyvalerate (PHBV) and bioglass (BG) have been widely reported to be suitable for bone tissue engineering. However, composite scaffolds with polymers and bioceramics have shown advantages over pure polymer and bioceramic scaffolds for bone tissue engineering. In addition, recent studies have shown that cross-talk between endothelial cells and osteoblastic cells can stimulate bone regeneration compared to tissue engineering constructs containing only one type of cell. Therefore, in this study, we aim to construct an improved engineered bone containing PHBV/BG composite scaffold with co-cultures of human umbilical vein endothelial cells (HUVECs) and human bone marrow stromal cells (HBMSCs) in order to enhance osteogenesis and angiogenesis of bone repair. Results showed that addition of BG into PHBV could enhance osteogenic differentiation of co-cultured HBMSCs and vascularization of co-cultured HUVECs by upregulating paracrine effects between the two types of cells compared to pure PHBV scaffolds. Among all groups, composite scaffolds containing PHBV with 10% BG showed the strongest stimulatory effects on osteogenic differentiation and vascularization due to their appropriate ion products, specifically, the appropriate concentration of silicon ions. In vivo results also demonstrated that PHBV containing 10% BG scaffolds with co-cultures of HUVECs and HBMSCs showed the strongest stimulatory effects on osteogenesis and angiogenesis among all groups. Taken together, PHBV/BG scaffolds with co-cultures of endothelial cells and osteogenic cells possess great application potential for bone tissue engineering.